Navigating survival in shifting landscapes: Women’s lived experiences with food, land, and water systems in climate-induced internal displacement in Zimbabwe - Maviza, Gracsious; Takaindisa, Joyce; Caroli, Giulia (University of KwaZulu-Natal, 2025)
This paper explores women's lived experiences navigating food, land, and water systems in the context of climate-induced displacement in Tsholotsho, Zimbabwe. Based on qualitative data generated through participatory methods, the paper signposts the effects of entrenched gender inequalities, shaped by patriarchal norms, in amplifying women’s vulnerabilities in climate shocks. However, despite the systemic inequalities, displaced women demonstrate resilience and agency through adaptive strategies to sustain their families through challenging times. Based on qualitative data generated through participatory methods, the paper explores women’s experiences in displacement. Using an intersectional approach, findings highlight their vulnerabilities, which include structural inequities, lack of access to land leading to disrupted livelihoods and challenges with access to water resources. They further underscore women’s agency and resilience, challenging dominant narratives that portray displaced women as passive victims.